Child labor between the international requirements and the enforcement of national laws: The Algerian law as a model - ATHMANI, Meriem (Journal of Human Sciences, 2025)
The national laws on child labor are a nexus between the international conventions that aim at ending or reducing child labor and the child that represents the most affected victim. In this context, the ratification of a specific convention by the Algerian legislator requires the enforcement of its principles, regarding either the absolute banning of child labor or the application of the rules on the child labor conditions; if work is a necessity imposed by the socioeconomic conditions of the child. The increase of this phenomenon shows the existence of activities that contradict with the international commitments and take place outside the legal frame. Therefore, it is necessary to investigate the legal texts on child labor in the Algerian law to find out more about the enforcement of the international conventions and about their efficiency in limiting this phenomenon.